Proton battery active material, preparation method and application thereof
Patent Information
- Application Number
- CN202611254196.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-27
AI Technical Summary
(1)本发明提供的质子电池活性材料的晶体结构可以为质子提供丰富存储位点和高效迁移通道,室温质子扩散系数远高于传统碳基材料,完美契合质子电池“质子嵌入-脱嵌”的核心工作机制,支撑快速充放电性能;
Smart Images

Figure CN122977438A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of proton battery technology, specifically to an active material for proton batteries, a preparation method thereof, and its applications. Background Technology
[0002] With the global energy structure transformation and the continued advancement of "dual-carbon" goals, the development and utilization of renewable energy sources such as wind and solar power are constantly expanding. However, due to the significant intermittency and volatility of renewable energy, their large-scale grid-connected application places higher demands on efficient, safe, and low-cost new energy storage technologies. Although traditional lithium-ion batteries have achieved commercial application, they are limited by factors such as uneven distribution of lithium resources, high cost, safety issues, and environmental impact, making it difficult to fully meet the development needs of future large-scale energy storage systems. Therefore, developing new green, efficient, and sustainable energy storage systems has become an important research direction in the current energy field.
[0003] The proton battery, as a novel rechargeable battery system, utilizes protons (H+) as its primary energy source. + As a current-carrying ion, protons possess characteristics such as small ionic radius, low diffusion resistance, and rapid kinetic response. Proton migration relies on the Grotthuss mechanism, where protons can rapidly hop between adjacent water molecules or other proton carriers via hydrogen bonding networks, thus achieving rapid proton migration. The proton migration rate can exceed that of lithium ions by 2-3 orders of magnitude, giving proton batteries the potential for rapid charge-discharge and high-rate performance. Furthermore, protons are widely available, supplied through water or acidic media, offering advantages such as abundant resources, environmental friendliness, and low carbon emissions throughout their lifecycle, making them a key candidate system for next-generation green energy storage technology.
[0004] Currently, the development of proton batteries is still limited by the performance of electrode materials, especially the proton storage capacity, structural stability, and ion transport efficiency of the anode material, which directly determine the battery's capacity and cycle performance. Among the many candidate anode materials for proton batteries, antimony-based materials have a high theoretical specific capacity (>1000 mAh g⁻¹). -1 Its suitable proton insertion / extraction potential (approximately -1.5 to 1.5 V vs. SHE) and abundant resource reserves have attracted widespread attention.
[0005] From a resource utilization perspective, my country possesses abundant antimony reserves, with proven reserves accounting for approximately 52% of the global total, making it one of the world's major antimony resource countries. However, current antimony resource utilization in my country is mainly concentrated on low-tech and low-value-added products such as metallic antimony and antimony oxide, while the development of high-performance antimony-based functional materials remains relatively insufficient. Therefore, developing novel antimony-based energy storage materials with high added value and excellent electrochemical performance is of great significance for promoting the high-value utilization of antimony resources.
[0006] Polyantimonic acid (PAA) is a typical antimony-based oxide material with a large amount of stable Sb-O framework in its crystal structure. PAA materials with a pyrochlore structure typically possess a three-dimensional open network structure and a polyhedral framework constructed from pentavalent antimony. This structure provides continuous ion migration channels, facilitating rapid proton diffusion. Furthermore, the abundant oxygen coordination environment in pyrochlore PAA provides active sites for proton adsorption and reversible intercalation, theoretically achieving a specific capacity exceeding 1000 mAh g⁻¹. -1 Therefore, it is considered a potential proton battery anode material with high capacity and fast kinetic characteristics.
[0007] However, existing polyantimonic acid materials still have certain shortcomings in practical applications, such as: (1) the crystal structure of traditional polyantimonic acid materials is difficult to control, resulting in a limited number of effective proton transport channels and room for improvement in rate performance; (2) the electronic conductivity of the material is poor, which limits the full utilization of its electrochemical active sites; (3) existing proton battery systems mostly use liquid acidic electrolytes, which have problems such as electrolyte leakage, strong corrosiveness and insufficient safety, thus limiting their practical application.
[0008] Therefore, there is an urgent need to develop a polyantimonic acid electrode material with a stable pyrochlore structure, high proton transport capacity and excellent cycle stability, and to further combine it with a solid electrolyte to construct a safe and high-performance solid proton battery system to meet the development needs of next-generation green energy storage technology. Summary of the Invention
[0009] To address the shortcomings of existing technologies, the present invention aims to provide a proton battery active material, its preparation method, and its application. By preparing a polyantimonic acid material with a pyrochlore crystal structure, a stable three-dimensional open oxygen framework structure is formed within the material, providing continuous proton migration channels and abundant proton adsorption active sites, thereby improving the material's proton storage capacity and the kinetic transport speed of electrochemical reactions. Applying the pyrochlore-type polyantimonic acid material to a proton battery establishes a high-capacity, high-rate, and high-stability proton energy storage system, thus solving the technical problems mentioned in the background art, such as insufficient proton storage capacity, slow ion transport kinetics, poor structural stability in existing proton batteries, and electrolyte leakage, strong corrosivity, and insufficient safety in traditional liquid proton batteries.
[0010] This invention is achieved through the following technical solution: A method for preparing a proton battery active material includes the following steps: S1. Disperse potassium pyroantimonate and urea in deionized water at a mass ratio of 0.1~10:5~100, and stir evenly in a constant temperature water bath at 60~120℃. The stirring speed is 200~500 r / min and the stirring time is 0.1~2 h to obtain a raw material mixed solution. S2. Add an organic solvent to the raw material mixture solution prepared in step S1 and stir until homogeneous to obtain a mixed solution; S3. Place the mixed solution prepared in step S2 into a hydrothermal reactor, raise the temperature from room temperature to 150-200℃ at a rate of 1-10℃ / min and keep it at that temperature for 6-24 h. After the reaction is complete, cool to room temperature, filter and collect the precipitate in the reactor, wash and dry at 50-90℃ for 4-24 h to obtain the proton battery active material.
[0011] As a further aspect of the present invention, in step S1, the mass ratio of potassium pyroantimonate, urea and deionized water is (1~20):(1~45):(1~2000); in step S2, the volume ratio of organic solvent to deionized water in step S1 is (0.1~20):(1~100).
[0012] Preferably, in step S1, the mass ratio of potassium pyroantimonate, urea, and deionized water is 1:(2~20):(100~200), including but not limited to 1:4:200, 6:25:1100, 3:8:300, and 4:9:400; in step S2, the volume ratio of the organic solvent to the deionized water in step S1 is 1:(1~100), including but not limited to 1:5, 1:10, 1:20, 1:100, 2:25, 2:150, 3:17, 3:20, 6:55, 7:65, and 8:75.
[0013] Preferably, in steps S1 and S2, the mass ratio of potassium pyroantimonate, urea, deionized water, and organic solvent is 16:90:3700:1822.
[0014] Preferably, in step S1, the water bath temperature is 65~90℃, including but not limited to 65℃, 70℃, 65℃, 80℃, 85℃, and 90℃; the stirring speed is 250~450 r / min, including but not limited to 250 r / min, 300 r / min, 350 r / min, 400 r / min, and 450 r / min; and the stirring time is 0.2~1.5 h, including but not limited to 0.2 h, 0.3 h, 0.4 h, 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1.0 h, and 1.5 h.
[0015] As a further aspect of the present invention, in step S2, the organic solvent is selected from any one or more combinations of methanol, ethanol, isopropanol, ethylene glycol, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, N,N-dimethylformamide, N,N-dimethylacetamide, hexamethylphosphoric triamine, tetrahydrofuran, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, acetonitrile, propionitrile, benzonitrile, dimethyl sulfoxide, acetone, toluene, and chloroform.
[0016] This invention provides a proton battery active material, prepared using the above-described method. The proton battery active material is pyrochlore-type polyantimonyic acid with the molecular formula H₂Sb. x O y ·nH2O, where 1≤x≤5, 1≤y≤6, and 1≤n≤5.
[0017] This invention provides an application of the above-mentioned proton battery active material in the preparation of proton battery electrodes.
[0018] The present invention provides a proton battery, comprising an electrode, a separator, and an electrolyte. The electrode includes a current collector and an electrode membrane disposed on at least one side of the current collector. The electrode membrane comprises the above-mentioned proton battery active material, a conductive agent, and a binder.
[0019] The electrode includes a positive electrode and a negative electrode, and the electrode film includes a positive electrode film corresponding to the positive electrode and a negative electrode film corresponding to the negative electrode; when the proton battery active material is used for the positive electrode film, the negative electrode includes at least one of polypyrrole (PPy), polyaniline (PANI), quinone derivatives (naphthoquinone, anthraquinone), tungsten oxide (WO3), molybdenum oxide (MoO3), titanium-based oxides (TiO2, H2Ti3O7), activated carbon (AC), graphene (RGO), carbon nanotubes (CNTs), and hard carbon / soft carbon materials; when the proton battery active material is used for the negative electrode film, the positive electrode includes at least one of manganese-based oxides, vanadium-based oxides, Prussian blue analogs, and organic quinone / nitrogenous aromatic hydrocarbon materials.
[0020] As a further aspect of the present invention, when the proton battery active material is used as the negative electrode film, the positive electrode also includes one or more of the following: antimony-based materials (Sb, Sb2O3), tin-based materials (Sn, SnO2), bismuth-based materials (Bi, Bi2O3), and phosphorus-based materials (red phosphorus, black phosphorus).
[0021] As a further aspect of the present invention, the electrolyte is selected from at least one of the following materials: Solid electrolyte: The solid electrolyte is selected from any one or more combinations of perfluorosulfonic acid membrane (Nafion), polybenzimidazole (PBI) / H3PO4 composite membrane, Nafion / carbon nanotube composite membrane, PBI / SAPO ceramic particle composite membrane, cationic covalent organic framework (COF), silica-alumina phosphate (SAPO), zirconium antimonate (ZrSb2O6), and cesium dihydrogen phosphate (CsH2PO4) and is used as a proton exchange membrane; Liquid electrolyte and diaphragm, wherein the liquid electrolyte is selected from any one or more combinations of heteropoly acids, sulfuric acid (H2SO4), phosphoric acid (H3PO4), dilute hydrochloric acid (HCl), acetic acid (CH3COOH), hydrobromic acid (HBr), hydroiodic acid (HI), and proton-type ionic liquids, and is used as an acidic electrolyte; the heteropoly acid includes, but is not limited to, phosphomolybdic acid (H3PMo). 12 O 40 The proton-type ionic liquid includes, but is not limited to, protonated bis(trifluoromethanesulfonyl)imide (HTFSI); the diaphragm includes, but is not limited to, glass fiber filter paper.
[0022] As a further embodiment of the present invention, at room temperature, the proton battery active material, conductive agent, binder and solvent are mixed and ground for 6-8 h to obtain an electrode slurry, and the obtained electrode slurry is coated on a current collector to form an electrode film. After drying at 50-80°C for 10-14 h, the positive electrode is obtained, wherein the mass ratio of the proton battery active material, conductive agent and binder is (5-8):(1-3):(1-2).
[0023] As a further aspect of the present invention, the current collector is a solid mesh with high electronic conductivity, and the solid mesh is selected from any one or a combination of several of conductive graphite mesh, titanium mesh, nickel mesh, molybdenum mesh, copper mesh, aluminum mesh, and stainless steel mesh; the conductive agent is selected from at least one of conductive graphite and conductive carbon black, and the conductive carbon black includes Ketjen black, acetylene black, and Cabot black; the binder is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate, and styrene-butadiene rubber.
[0024] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: (1) The crystal structure of the proton battery active material provided by the present invention can provide abundant storage sites and efficient migration channels for protons. The room temperature proton diffusion coefficient is much higher than that of traditional carbon-based materials, which perfectly matches the core working mechanism of proton battery "proton insertion-deintercalation" and supports fast charge and discharge performance; (2) The antimony element Sb in the proton battery active material provided by the present invention 3+ / Sb 5+ Its multivalent state characteristics endow it with a high redox potential, and its discharge specific capacity reaches 1100 mAh g. -1It is significantly higher than that of the mainstream organic electrode material TABQ (approximately 120 mAh g⁻¹). -1 It exhibits strong corrosion resistance in the acidic H2SO4 / H3PO4 electrolyte of proton batteries, which can solve the dissolution and corrosion problems of traditional metal-based electrodes; the volume change during proton insertion / extraction is small, which can effectively avoid electrode structure deformation and ensure the long-term cycle stability of the battery; both the electrode material and the electrolyte material have good compatibility, which can reduce the contact loss at the electrode-electrolyte interface and improve the energy conversion efficiency of the battery. (3) The proton battery active material provided by the present invention is prepared in one step by using potassium pyroantimonate and urea as raw materials and a solvothermal method. The preparation process is simple, safe and environmentally friendly. It does not require complicated pretreatment and subsequent calcination modification. Moreover, no toxic by-products are generated in the reaction process. The ammonia nitrogen generated by the decomposition of urea can regulate the crystal growth of the material. The product has high purity and can be used for large-scale production. (4) The proton battery active material provided by the present invention has a unique three-dimensional open framework structure. Compared with traditional layered polyantimonic acid, it has good performance balance, high specific surface area and theoretical specific capacity, good rate performance and cycle stability, and can provide rich active sites for proton storage. It has broad application prospects in the large-scale production of proton batteries. Attached Figure Description
[0025] To more clearly illustrate the technical solutions of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 This is an optical photograph of pyrochlore-type polyantimony acid, the active material for proton batteries provided by this invention, at room temperature. Figure 2 This is the powder X-ray diffraction (XRD) pattern of pyrochlore-type polyantimonic acid, the active material for proton batteries provided by this invention; Figure 3 This is a crystal structure diagram of pyrochlore-type polyantimonic acid, the active material for proton batteries provided by this invention. Figure 4 This is a scanning electron microscope (SEM) image of pyrochlore-type polyantimonic acid, the active material for proton batteries provided by this invention. Figure 5 This is the BET detection spectrum of the specific surface area of pyrochlore-type polyantimony acid, an active material for proton batteries, provided by this invention. Figure 6 This is the full X-ray photoelectron spectroscopy (XPS) spectrum of pyrochlore-type polyantimony acid, an active material for proton batteries provided by this invention. Figure 7 This is a rate capability diagram of pyrochlore-type polyantimony acid, the proton battery active material provided by this invention, in a half-cell. Figure 8 This is a long charge-discharge cycle diagram of pyrochlore-type polyantimony acid, the proton battery active material provided by this invention, in a half-cell. Figure 9 This is a charge-discharge long-cycle diagram of the proton battery provided in Embodiment 9 of the present invention; Figure 10 This is a comparison of powder X-ray diffraction (XRD) images of the products provided in Example 1 and Comparative Example 1 of the present invention. Detailed Implementation
[0027] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] Unless otherwise specified, the raw materials and reagents used in the examples are readily available commercially, and the experimental methods used are performed in accordance with the manufacturer's instructions or are conventional techniques in the art. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as are familiar to one skilled in the art.
[0029] Example 1 This embodiment provides a method for preparing active materials for proton batteries. The mass ratio of potassium pyroantimonate, urea, and deionized water is 1:6:100~120, and the preparation steps are as follows: S1. Disperse 0.32 g potassium pyroantimonate and 0.8 g urea in 37 mL of deionized water and stir evenly in a 90℃ constant temperature water bath at a stirring speed of 500 r / min for 0.3 h to obtain a raw material mixed solution. S2. Add 23 mL of methanol to the raw material mixture solution prepared in step S1 and stir until homogeneous to obtain a mixed solution; S3. The mixed solution prepared in step S2 is placed in a hydrothermal reactor and heated from room temperature to 170°C at a rate of 5°C / min and kept at that temperature for 12 h. After the reaction is completed, it is naturally cooled to room temperature. The precipitate in the reactor is collected by filtration, washed with deionized water, and dried at 60°C for 12 h to obtain the proton battery active material with a yield of 90%. According to the comparison of powder X-ray diffraction data and standard cards, the impurity content is 1%.
[0030] This embodiment also provides a proton battery active material prepared by the above preparation method, such as... Figure 1 As shown in the optical photograph at room temperature, the prepared proton battery active material is a white powder solid. The obtained material was subjected to X-ray diffraction (XRD) testing, and the results are as follows: Figure 2 As shown, the diffraction peak positions of the prepared proton battery active material are consistent with those of the standard card, indicating that the polyantimony acid (PAA) prepared in this embodiment possesses the following properties: Figure 3 The pyrochlore-type crystal structure shown.
[0031] The pyrochlore-type polyantimonyic acid prepared in this embodiment was subjected to scanning electron microscopy, specific surface area measurement, and X-ray photoelectron spectroscopy (XPS) detection. The detection results are as follows: Figure 4 , Figure 5 , Figure 6 As shown, by Figure 4-5 It can be seen that the pyrochlore-type polyantimony acid particles prepared in this embodiment are relatively large and uniformly distributed, with a particle size of 0.4~1.7 μm and a specific surface area of 40.799 m². 2 / g. Combined with XRD pattern ( Figure 2 ) and XPS graph ( Figure 6 As can be seen, the proton battery active material prepared in this embodiment is pyrochlore-type polyantimony acid (PAA), with the molecular formula H2Sb2O6·nH2O, where 1≤n≤5.
[0032] Example 2 This embodiment provides a method for preparing a proton battery active material. The mass ratio of the raw materials potassium pyroantimonate, urea and deionized water is 1:2.5:100~120. The preparation method is basically the same as that in Example 1, except that 0.8 g of urea is used as the raw material. The remaining steps are the same as in Example 1, and the corresponding proton battery active material is finally prepared.
[0033] This invention provides a proton battery active material prepared by the above preparation method. The obtained proton battery active material is pyrochlore-type polyantimony acid (PAA), and its structure and molecular formula are consistent with those in Example 1.
[0034] Example 3 This embodiment provides a method for preparing a proton battery active material. The mass ratio of the raw materials potassium pyroantimonate, urea and deionized water is 1:7.5:100~120. The preparation steps are basically the same as those in Example 1, except that 2.4 g of urea is used as the raw material. The remaining steps are the same as those in Example 1, and the corresponding proton battery active material is finally prepared.
[0035] This invention provides a proton battery active material prepared by the above preparation method. The obtained proton battery active material is pyrochlore-type polyantimony acid (PAA), and its structure and molecular formula are consistent with those in Example 1.
[0036] Example 4 This embodiment provides a method for preparing a proton battery active material. The mass ratio of potassium pyroantimonate, urea and deionized water is 1:16:100~120. The preparation steps are basically the same as in Example 1, except that 5.1 g of urea is used as the raw material. The remaining steps are the same as in Example 1, and the corresponding proton battery active material is finally prepared.
[0037] This invention provides a proton battery active material prepared by the above preparation method. The obtained proton battery active material is pyrochlore-type polyantimony acid (PAA), and its structure and molecular formula are consistent with those in Example 1.
[0038] Example 5 This embodiment provides a method for preparing a proton battery active material. The mass ratio of the raw materials potassium pyroantimonate, urea and deionized water is 1:(10~12):(100~120). The preparation steps are basically the same as in Example 1, except that 3.7 g of urea is used as the raw material. The remaining steps are the same as in Example 1, and the corresponding proton battery active material is finally prepared.
[0039] This invention provides a proton battery active material prepared by the above preparation method. The obtained proton battery active material is pyrochlore-type polyantimony acid (PAA), and its structure and molecular formula are consistent with those in Example 1.
[0040] Example 6 This embodiment provides a method for preparing a proton battery active material. The preparation steps are basically the same as those in Example 1. The difference is that in step S2, the organic solvent is replaced by ethanol instead of methanol, and the volume ratio of ethanol to deionized water in step S1 is 1:5. The remaining steps are the same as those in Example 1, and the corresponding proton battery active material is finally prepared.
[0041] This invention provides a proton battery active material prepared by the above preparation method. The obtained proton battery active material is pyrochlore-type polyantimony acid (PAA), and its structure and molecular formula are consistent with those in Example 1.
[0042] Example 7 This embodiment provides a method for preparing a proton battery active material. The preparation steps are basically the same as those in Example 1. The difference is that in step S2, dimethyl carbonate is used instead of methanol as the organic solvent, and the volume ratio of dimethyl carbonate to deionized water in step S1 is 1:10. The remaining steps are the same as those in Example 1, and the corresponding proton battery active material is finally prepared.
[0043] This invention provides a proton battery active material prepared by the above preparation method. The obtained proton battery active material is pyrochlore-type polyantimony acid (PAA), and its structure and molecular formula are consistent with those in Example 1.
[0044] Example 8 This embodiment provides a method for preparing a proton battery active material. The preparation steps are basically the same as those in Example 1. The difference is that in step S2, the organic solvent is replaced by a toluene-chloroform mixture (volume ratio 1:1), and the volume ratio of the toluene-chloroform mixture to the deionized water in step S1 is 3:17. The remaining steps are the same as those in Example 1, and the corresponding proton battery active material is finally prepared.
[0045] This invention provides a proton battery active material prepared by the above preparation method. The obtained proton battery active material is pyrochlore-type polyantimony acid (PAA), and its structure and molecular formula are consistent with those in Example 1.
[0046] Example 9 This embodiment provides an aqueous proton battery, including a positive electrode, a negative electrode, a separator, and an electrolyte, and its preparation process is as follows: Preparation of negative electrode: The negative electrode includes a conductive graphite mesh (as a current collector) and an electrode film disposed on at least one side of the conductive graphite mesh. The electrode film includes polyantimony acid, conductive graphite (as a conductive agent), and sodium carboxymethyl cellulose (as a binder), which are active materials for proton batteries prepared in Example 1. The active materials for proton batteries prepared in Example 1, polyantimony acid, conductive graphite, and sodium carboxymethyl cellulose are mixed with methanol in a mass ratio of 6:3:1:300 and ground into an electrode slurry. The slurry is then coated onto the current collector to form an electrode film. After drying, the negative electrode is obtained. Preparation of the positive electrode: 4 g of vanadium pentoxide (V2O5) was dissolved in 50 mL of hydrochloric acid (HCl) and diluted to 75 mL with deionized water. 700 µL of glycerol was added dropwise to the solution while stirring continuously to obtain a clear blue vanadium precursor solution. 9.375 mL of the precursor solution was taken and diluted to 50 mL with deionized water to obtain a transparent blue solution, denoted as solution A. 1.18 g of potassium ferricyanide K3[Fe(CN)6] was dissolved in 50 mL of deionized water to obtain a potassium ferricyanide solution, denoted as solution B. Under vigorous magnetic stirring, solution B was added dropwise to solution A to obtain a mixture. The mixture was heated at 60 °C for 9 hours. After the reaction was completed, it was cooled to room temperature. The resulting green precipitate was collected by centrifugation, thoroughly washed with deionized water and ethanol, and dried at 80 °C to obtain the product vanadium hexacyanoferrate. The obtained vanadium hexacyanate ferrite, conductive additive Super P, and binder polytetrafluoroethylene were mixed evenly in ethanol at a mass ratio of 7:2:1. After drying, the mixture was pressed into a form with an active material loading of approximately 2 mg / cm³.-2 The thin film was dried under vacuum at 60°C; finally, the obtained film was pressed onto a titanium mesh current collector by a roller press to prepare the positive electrode.
[0047] Using the negative and positive electrodes prepared above, a proton battery was constructed with glass fiber filter paper as the separator and phosphoric acid with a concentration of 9 mol / L as the electrolyte.
[0048] Example 10 This embodiment provides an aqueous proton battery, the preparation method of which is largely the same as that of Example 9, except that the electrolyte used is a phosphoric acid-sulfuric acid mixed solution. The phosphoric acid-sulfuric acid mixed solution is prepared by dissolving phosphoric acid and sulfuric acid in deionized water at a 1:1 mass ratio to form a mixed acid electrolyte with a concentration of 1.0 mol / L. The remaining steps are the same as in Example 9. Since sulfuric acid can provide a high concentration of free protons, increasing the ionic conductivity of the electrolyte, and phosphoric acid has a strong ability to build hydrogen bond networks, promoting proton hopping transport, the composite electrolyte provided in this embodiment is beneficial for improving the battery's rate performance and cycle stability.
[0049] Example 11 This embodiment provides an aqueous proton battery, the preparation method of which is largely the same as that of Example 9, except that the electrolyte used is a phosphoric acid-sulfuric acid-phosphomolybdic acid mixed solution. The phosphoric acid-sulfuric acid-phosphomolybdic acid mixed solution is prepared by dissolving phosphoric acid, sulfuric acid, and phosphomolybdic acid in deionized water at a mass ratio of 5:2:1 to form a mixed solution with a concentration of 1.0 mol / L. The remaining steps are the same as in Example 9. Since sulfuric acid can provide a high concentration of free protons, improving the ionic conductivity of the electrolyte; phosphoric acid has a strong ability to build hydrogen bond networks, promoting proton hopping transport; and phosphomolybdic acid, as a polyacid structure, can provide additional proton storage sites and enhance interfacial stability, the composite electrolyte provided in this embodiment is beneficial for improving the battery's rate performance and cycle stability.
[0050] Example 12 This embodiment provides an aqueous proton battery, the preparation method of which is largely the same as that of Example 10, except that the mass ratio of phosphoric acid to sulfuric acid is 2:1, and the remaining steps are the same as those of Example 10.
[0051] Example 13 This embodiment provides an aqueous proton battery, the preparation method of which is largely the same as that of Example 10. The difference is that the electrolyte system used is phosphoric acid and phosphotungstic acid, wherein the mass ratio of phosphoric acid to sulfuric acid is 2:1, and the remaining steps are the same as those of Example 10.
[0052] Example 14 This embodiment provides an aqueous proton battery, the preparation method of which is largely the same as that of Example 10. The difference is that the electrolyte system used is phosphoric acid and phosphomolybdic acid, wherein the mass ratio of phosphoric acid to phosphomolybdic acid is 3:1. The remaining steps are the same as those in Example 10.
[0053] Example 15 This embodiment provides an aqueous proton battery, the preparation method of which is largely the same as that of Example 10, except that the electrolyte system used is phosphoric acid, and the other steps are the same as those of Example 10.
[0054] Electrochemical tests were performed on the aqueous proton batteries provided in Examples 10-15. The main mechanisms of action and electrochemical performance characteristics of the different electrolyte systems provided in Examples 10-15 in aqueous proton batteries are shown in Table 1.
[0055] Table 1 - Performance Comparison of Aqueous Proton Batteries Provided in Examples 7-12: Example 10 <![CDATA[H2SO4-H3PO4(1:1)]]> Benchmark system benchmark performance Example 11 <![CDATA[H3PO4-H2SO4-H3PMo 12 THE 40 ]]> High proton concentration + heteropolyacid proton storage + hydrogen bond network Best overall performance, highest capacity retention and cycle stability Example 12 <![CDATA[H2SO4-H3PO4(1:2)]]> Increase proton conductivity and reduce water activity High initial capacity and good cycling performance Example 13 <![CDATA[H3PO4-H3PW 12 THE 40 ]]> Heteropolyacids promote proton migration Superior rate performance and enhanced interface stability Example 14 <![CDATA[H2SO4-H3PMo 12 THE 40 ]]> Fast proton transport + multiacid buffer Outstanding performance at high magnification Example 15 <![CDATA[H3PO4]]> Stabilize the hydrogen bond network and suppress side reactions It has a long cycle life, but limited rate performance. As shown in Table 1, based on Example 10, the phosphoric acid-sulfuric acid-phosphomolybdic acid mixed electrolyte system provided in Example 11 has the best overall performance, with the highest capacity retention and cycle performance stability.
[0056] Example 16 This embodiment provides an aqueous proton battery, the preparation method of which is largely the same as that of Example 9, except that the electrolyte used is a phosphoric acid-sulfuric acid-bis(trifluoromethanesulfonyl)imide mixed solution. Phosphoric acid, sulfuric acid, and protonated bis(trifluoromethanesulfonyl)imide are dissolved in deionized water in a 1:1:1 mass ratio to form a mixed solution with a concentration of 1.0 mol / L. The remaining steps are the same as in Example 9. Since sulfuric acid can provide a high concentration of free protons, increasing the ionic conductivity of the electrolyte; phosphoric acid has a strong ability to build hydrogen bond networks, which can promote proton hopping transport; and the bis(trifluoromethanesulfonyl)imide group has a strong electron attraction ability and a large spatial structure, which can reduce the activity of water molecules and improve the stability of the electrolyte system by adjusting the ion solvation structure in the electrolyte. It also helps to construct a more stable proton transport environment. The composite electrolyte provided in this embodiment is beneficial for improving the battery's rate performance and cycle stability.
[0057] Example 17 This embodiment provides an aqueous proton battery, the preparation method of which is largely the same as that of Example 9, except that the electrolyte used is a solid electrolyte perfluorosulfonic acid membrane (Nafion), and the remaining steps are the same as those of Example 9.
[0058] Example 18 This embodiment provides an aqueous proton battery, the preparation method of which is largely the same as that of Example 9. The difference is that the electrolyte used is a solid electrolyte polybenzimidazole (PBI) / H3PO4 composite membrane, and the remaining steps are the same as those of Example 9.
[0059] Example 19 This embodiment provides a half-cell, the preparation method of which is largely the same as that of Example 9. The difference is that the polyantimony-containing electrode prepared in Example 9 is used as the working electrode, and activated carbon (AC) is used as the counter electrode. The preparation method of the counter electrode is as follows: activated carbon, Ketjen black and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 7:2:1, and an appropriate amount of N-methylpyrrolidone (NMP) solvent is added (solid-liquid ratio of 1:20~40). The mixture is stirred thoroughly to form a uniform slurry. The slurry is coated on the surface of carbon cloth and dried in a vacuum oven at 60°C to obtain the counter electrode.
[0060] The prepared working electrode, counter electrode, separator (glass fiber filter paper), and electrolyte (9 mol / L phosphoric acid) were sequentially assembled into a CR2032 button cell casing to form a half-cell. A LAND CT2001 battery testing system was used to perform constant current charge-discharge (GCD) tests on the half-cell. The specific capacity of the battery was calculated based on the mass of the working electrode materials. The test results are as follows: Figure 7 , 8 As shown.
[0061] At 0.1 A g -1 0.2 A g -1 0.5 A g -1 1 A g -1 2A g -1 0.1 A g -1 Rate performance was tested at current density, and the results are as follows: Figure 7 As shown. By Figure 7 It can be seen that at 0.1 Ag -1 and 2 A g -1 The sample prepared by this invention under high current density has a concentration of 900 mAh g. -1 and 270 mAh g -1 The high discharge specific capacity fully demonstrates that pyrochlore-type polyantimony acid has excellent rate capability in half-cells.
[0062] At 0.1 A g -1 The charge-discharge specific capacity was tested under cyclic current density, and the results are as follows: Figure 8 As shown, at 0.1 Ag -1 At a current density of [value missing], the sample prepared in this invention still retains 1100 mAh g after 2640 hours of charge-discharge cycling. -1The high discharge specific capacity fully demonstrates that pyrochlore-type polyantimony acid has good electrochemical cycling stability in half-cells.
[0063] In 20 A g -1 At a current density of [value missing], the charge-discharge specific capacity of the aqueous proton battery provided in Example 9 was tested under cyclic conditions, and the results are as follows: Figure 9 As shown, at 20 A g -1 At a current density of [value missing], the sample prepared in this invention still retains 95 mAh g⁻¹ after 2000 charge-discharge cycles. -1 The high discharge specific capacity fully demonstrates that pyrochlore-type polyantimony acid has good electrochemical cycle stability in aqueous proton batteries.
[0064] Comparative Example 1 Comparative Example 1 provides a method for preparing an active material, which is largely the same as Example 1, except that urea is not used in the raw materials, and all other steps are the same as in Example 1.
[0065] The product prepared in Comparative Example 1 was subjected to the same X-ray diffraction (XRD) test as in Example 1. The diffraction peak positions of the active material prepared in Comparative Example 1 were compared with those of Example 1 and the standard card, respectively. The comparison results are as follows: Figure 10 As shown. By Figure 10 It is evident that polyantimony (PAA) was not obtained in Comparative Example 1. Therefore, urea is an essential raw material in this invention; without urea, polyantimony (PAA) cannot be prepared.
[0066] In summary, this invention utilizes potassium pyroantimonate and urea as raw materials to prepare polyantimonate for proton batteries in a one-step solvothermal process. The preparation process is simple, energy-efficient, requires no complex pretreatment or subsequent calcination modification, and generates no toxic byproducts, resulting in high product purity. The polyantimonate proton battery active material prepared by this invention possesses a unique three-dimensional open framework structure, providing abundant storage sites and efficient migration channels for protons, achieving a room-temperature proton diffusion coefficient of 5 × 10⁻⁶. -7 cm 2 / s) is far higher than that of traditional carbon-based materials (10 -8 ~10 -9 cm 2 The material ( / s) perfectly matches the core working mechanism of proton batteries, namely "proton insertion-deintercalation". The volume change rate during proton insertion / deintercalation is less than 5%, which can effectively avoid electrode structure deformation, support fast charge and discharge performance, and ensure the long-cycle stability of the battery. Both the material and the electrolyte material have good compatibility, which can reduce the contact loss at the electrode-electrolyte interface and improve the energy conversion efficiency of the battery.
[0067] Furthermore, the proton battery active material provided by this invention exhibits good performance balance, with antimony element Sb 3+ / Sb 5+ Its multivalent state characteristics endow it with a high redox potential of approximately 1.5 V vs. SHE, which can boost the output voltage of proton batteries to over 3 V. The sample prepared in this invention still retains 1100 mAh g after long-term charge-discharge cycles. -1 Its high discharge specific capacity is significantly higher than that of traditional layered polyantimony acid and mainstream organic electrode material TABQ (approximately 120 mAh g⁻¹). -1 It exhibits strong corrosion resistance in the acidic H2SO4 / H3PO4 electrolyte of proton batteries, which can solve the dissolution and corrosion problems of traditional metal-based electrodes, and has broad application prospects in the large-scale production of proton batteries.
[0068] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a proton battery active material, characterized in that, Includes the following steps: S1. Disperse potassium pyroantimonate and urea in deionized water at a mass ratio of (0.1~10):(5~100), and stir evenly in a constant temperature water bath at 60~120℃. The stirring speed is 200~500 r / min, and the stirring time is 0.1~2 h to obtain a raw material mixed solution. S2. Add an organic solvent to the raw material mixture solution prepared in step S1 and stir until homogeneous to obtain a mixed solution; S3. Place the mixed solution prepared in step S2 into a hydrothermal reactor, raise the temperature from room temperature to 150-200℃ at a rate of 1-10℃ / min and keep it at that temperature for 6-24 h. After the reaction is complete, cool to room temperature, filter and collect the precipitate in the reactor, wash and dry at 50-90℃ for 4-24 h to obtain the proton battery active material.
2. The method for preparing the proton battery active material according to claim 1, characterized in that, In step S1, the mass ratio of potassium pyroantimonate, urea and deionized water is (1~20):(1~45):(1~2000); in step S2, the volume ratio of organic solvent to deionized water in step S1 is (0.1~20):(1~100).
3. The method for preparing the proton battery active material according to claim 1, characterized in that, In step S2, the organic solvent is selected from any one or more combinations of methanol, ethanol, isopropanol, ethylene glycol, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, N,N-dimethylformamide, N,N-dimethylacetamide, hexamethylphosphoric triamine, tetrahydrofuran, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, acetonitrile, propionitrile, benzonitrile, dimethyl sulfoxide, acetone, toluene, and chloroform.
4. A proton battery active material, characterized in that, The proton battery active material is prepared by the preparation method described in any one of claims 1 to 3, and is pyrochlore-type polyantimonyic acid with the molecular formula H2Sb. x O y ·nH2O, where 1≤x≤5, 1≤y≤6, and 1≤n≤5.
5. The application of the proton battery active material as described in claim 4 in the preparation of proton battery electrodes.
6. A proton battery, characterized in that, The battery includes electrodes, a separator, and an electrolyte. The electrodes include a current collector and an electrode membrane disposed on at least one side of the current collector. The electrode membrane includes the proton battery active material, conductive agent, and binder as described in claim 4.
7. The proton battery according to claim 6, characterized in that, The electrode includes a positive electrode and a negative electrode, and the electrode film includes a positive electrode film corresponding to the positive electrode and a negative electrode film corresponding to the negative electrode; when the proton battery active material is used for the positive electrode film, the negative electrode includes at least one of polypyrrole, polyaniline, quinone derivatives, tungsten oxide, molybdenum oxide, titanium-based oxide, activated carbon, and hard carbon / soft carbon materials; when the proton battery active material is used for the negative electrode film, the positive electrode includes at least one of manganese-based oxide, vanadium-based oxide, Prussian blue analogue, and organic quinone / nitrogenous aromatic hydrocarbon materials.
8. The proton battery according to claim 6, characterized in that, The electrolyte is selected from any one or more combinations of cationic covalent organic frameworks, silica-alumina phosphate, perfluorosulfonic acid membranes, polybenzimidazole / H3PO4 composite membranes, perfluorosulfonic acid / carbon nanotube composite membranes, polybenzimidazole / silica-alumina phosphate ceramic particle composite membranes, zirconium antimonate, cesium dihydrogen phosphate, heteropoly acids, sulfuric acid, phosphoric acid, hydrochloric acid, acetic acid, hydrobromic acid, hydroiodic acid, and proton-type ionic liquids; the heteropoly acid includes phosphomolybdic acid; the proton-type ionic liquid includes protonated bis(trifluoromethanesulfonyl)imide; and the membrane includes glass fiber filter paper.
9. The proton battery according to claim 6, characterized in that, At room temperature, the proton battery active material, conductive agent, binder and solvent are mixed and ground for 6-8 h to obtain an electrode slurry. The obtained electrode slurry is then coated onto a current collector to form an electrode film. After drying at 50-80°C for 10-14 h, the positive electrode is obtained. The mass ratio of the proton battery active material, conductive agent and binder is (5-8):(1-3):(1-2).
10. The proton battery according to claim 9, characterized in that, The current collector is selected from any one or a combination of several of conductive graphite mesh, titanium mesh, nickel mesh, molybdenum mesh, copper mesh, aluminum mesh, and stainless steel mesh; the conductive agent is selected from at least one of conductive graphite and conductive carbon black, and the conductive carbon black includes Ketjen black, acetylene black, and Cabot black; the binder is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate, and styrene-butadiene rubber.